KAJIAN FUNGSI ORNAMEN RUMAH TRADISIONAL KAMPUNG ARAB AL-MUNAWWAR - Mukhsin Patriansyah; Yayan Hariansyah (INJECT (Interdisciplinary Journal of Communication), 2018)
The long journey of ornamental activity decorates the ancestors of South Sumatra who have given birth to various kinds of ornaments which are a reflection of their culture and natural environment to get outside influences through animism and dynamism, Hinduism and Islamization. The transition of the era has a major contribution to the ornamental activities of the ancestors of South Sumatra who experienced development and change. Islamic teachings have a major influence on the function and creation of traditional house ornaments in the Al-Munawwar village of Palembang, this can be seen from the motifs used which are sourced from nature. In its realization, the motif has been stylized in shape, so that the ornaments produced differ greatly from the original form. Arab Al-Munawwar villagers use ornaments to add aesthetic value to their residential buildings. The use of these ornaments can be seen from several sides such as doors, windows, ventilation, walls, room dividers, poles and so on. Does not rule out the possibility in the form of traditional house ornaments Arab Al-Munawwar village stored messages and meanings that are interesting to explore. The study in this study focuses more on aesthetic values, with the aim of tracing the structure that builds and expresses the symbolic values implied in the traditional house ornaments of the Al-Munawwar Arabian village of Palembang. The research method used is a qualitative method, with analytic descriptive analysis. The data is then identified, classified, selected, then analyzed and interpreted according to the text and context. AbstrakMasyarakat Kampung Arab Al-Munawwar memanfaatkan ornamen untuk menambah nilai estetis dari bangunan tempat tinggal mereka. Penggunaan ornamen ini bisa dilihat dari beberapa sisi seperti pintu, jendela, ventilasi, dinding, penyekat ruangan, tiang dan lain sebagainya. Tidak menutup kemungkinan di dalam wujud ornamen rumah tradisional Kampung Arab Al-Munawwar tersimpan pesan dan makna yang manarik untuk di telusuri. Kajian dalam penelitian ini lebih menitikberatkan pada nilai estetika, dengan tujuan untuk menelusuri struktur yang membangun dan mengungkapkan nilai simbolik yang tersirat dalam ornamen rumah tradisional Kampung Arab Al-Munawwar Palembang. Metode penelitian yang digunakan adalah metode kualitatif, dengan analisis deskriptif analitik. Data tersebut kemudian diidentifikasikan, diklasifikasi, diseleksi, selanjutnya dianalisis dan diinterpretasikan sesuai teks dan konteksnya.